The Impact of Trade Secrets on Innovation and Product Development in the Technology Industry - Topan Ahmad Anhari Harahap; Nazwa Fitriana; Cita Suci; Ilham Maylandi Damanik; M. Faiz Almaisi; Meldyana Permata (Jurnal Cendikia ISNU SU, 2024)
Trade secrets are information in the technology and/or business sectors that is not publicly known, has economic value, and is kept confidential by its owner. In the technology industry, trade secrets play a crucial role in driving innovation and product development. Protecting strategic information such as formulas, designs, algorithms, and production methods enables companies to maintain a competitive advantage amidst increasingly dynamic market competition. This study highlights the impact of trade secret protection on the sustainability of innovation and product development processes, while also emphasizing the importance of effective legal mechanisms to safeguard high-value information to drive sustainable growth in the technology industry.